Legal Protection for Banks as Warehouse Receipt Holders of Bankrupt Agricultural Products - Arizal Pratama, Mohammad; Triyanto, Toni (Jurnal Konstatering, 2025)
This research is entitled "Legal Protection for Banks as Holders of Warehouse Receipts for Bankrupt Agricultural Products." The background of this research stems from the problem of farmers' limited access to capital, which has led to the emergence of the warehouse receipt system as an agricultural-based financing instrument. Warehouse receipts can be used as collateral for credit at banks, but they give rise to legal issues when the debtor goes bankrupt. Banks, as holders of warehouse receipts, face legal, economic, and institutional risks in their efforts to obtain repayment of receivables. The research problem is formulated in three main points: (1) what is the legal force of agricultural warehouse receipts in bankruptcy; (2) what form of legal protection is available for banks as holders of agricultural warehouse receipts that are bankrupt; and (3) what obstacles do banks face in obtaining this legal protection. The research method used was empirical with a descriptive analytical approach. Primary data was obtained through interviews with banking institutions and the Warehouse Receipt Guarantee Institution, while secondary data was obtained through a review of relevant laws and regulations, doctrine, and literature. The analysis was conducted qualitatively and normatively, connecting legal theory with implementation practice. The results of the study indicate that warehouse receipts have legal force as securities that can be used as collateral for debt, and in bankruptcy their position is equal to material collateral, thus placing banks as separatist creditors. Legal protection for banks is provided through the provisions of Law No. 9 of 2011 concerning Warehouse Receipts and Law No. 37 of 2004 concerning Bankruptcy and PKPU, which allow banks to execute collateral objects before they are distributed to other creditors. However, there are obstacles in the form of limited economic value of agricultural products, lack of understanding of warehouse receipts among law enforcement officials and banks, convoluted bureaucracy, and the weak role of the Warehouse Receipt Guarantee Institution. In conclusion, legal protection for banks as holders of agricultural warehouse receipts in bankruptcy is already stipulated in legislation, but its implementation still faces various normative and practical obstacles. Therefore, regulatory strengthening, capacity building of financial institutions and law enforcement, and optimization of the role of the Warehouse Receipt Guarantee Institution are needed to ensure that warehouse receipts can function effectively as credit collateral.